Factors related to infant mortality for congenital anomalies, Paraná, Brazil 2010-2019 (Research, Society and Development, 2021)
Objective: to investigate the factors related to infant deaths due to congenital anomalies in the municipalities belonging to the 14th Regional Health Region of Paraná, in the period from 2010 to 2019. Methodology: cross-sectional study based on secondary data from the Born Information System Living, Mortality Information System and Notifiable Diseases Information System. Results: the detection of anomalies before hospital discharge proved to be a protective factor against death. The following factors were associated with death: children with low birth weight (OR= 5.7, 95%CI= 3.37-9.77, p